Physical activity and dietary habits in portuguese college students - Carvalho, Ana (2013)
The present study aimed to investigate the association between time spent on the practice of physical activity and dietary habits in college students. This is a transversal and correlational study, which has a sample of 121 students aged between 18 and 28 years old. Data were collected through three questionnaires, socio-demographic, time management and food diary; the latter two were fi lled for 3 days. Subsequently, a descriptive and inferential statistical analysis was used. To investigate the association between time spent on the practice of physical activity and dietary habits in college students we used the test of Spearman correlation and Kendall´s test, assuming a confidence interval of 95%. 81.8% of the sample were female and 18.2% male. About the practice of physical activity it was found that 21% were sedentary/low active and 79% active/very active. From the active/very active students 88,5% revealed a non-recommended intake of fat and all of the sedentary/low active students presented a non-recommended consumption of protein. From the present results it can be concluded that dietary habits are not correlated with time spent on physical activity. Such as this study,Ottevaere et al. (2011) concluded that no statistical differences were found in energy intake between the levels of physical activity but they observed an inverse association between the consumption of cereal and physical activity level. Many studies observed positive associations between the consumption of fi ber and protein and physical activity level. These results are in discrepancy with our findings. So, it is noteworthy that longitudinal studies are necessary to examine the energy balance among these students to obtain more accurate conclusions.